Dispersion Degree and its Influence on Structure of Building Materials. Issue 3 (February 2019) - Yakovlev, Grigory; Grakhov, Valery; Polyanskih, Irina; Gordina, Anastasiya; Pudov, Igor; Mohhamed, Ali; Karpova, Ekaterina; Saraykina, Kseniya; Saidova, Zarina
Abstract: The main basic characteristic of building materials which determines physical and technical properties of composites is structure. However, it is difficult to provide certain conditions for structure formation. For this purpose, it is possible to create space-limited environment for coagulation of submicroscopic crystals. Generally, this effect is caused by addition of high-dispersed components, usually carbon nanotubes, graphens and etc. are used. The results show that the more effective way is to use the combination of ultra- and nanofine additives and in this case nanofine additives should have specific chemical relation to the binder. Fume silica, surfactants ("Ethacryl HF", "DC-5" including multiwall carbon nanotubes) were used for modification of building materials. In order to replace multiwall carbon nanotubes water suspension of furnace black (trade mark Palizh, Izhevsk) was added into cement matrix. When the ultrafine additive (silica fume) combines to nanofine components there is great increase of material performances. 0.5% "Ethacryl HF" and "DC-5" with 3% silica fume allow achieving compressive strength to 79.2 % and flexural strength to 94, 6% accordingly (compare to test sample). To establish effect from additives and its generality gypsum binder was used. Additionally, the dispersion degrees, mineral chemistry, nature of microfine components are found to be important for modification of building materials. Nanofine additives which have chemical relation to the binder in mineral matrix also have active surfaces and on these surfaces are formed layers of new crystals. The high surface energy of nanofines reduces re-crystallization and allows creating high density and freeing from defects matrixes. Generality of this effect which include all mineral binders is proved.